2023
DOI: 10.1097/md.0000000000034842
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of acupuncture or moxibustion in treating senile insomnia compared with a control group: A systematic review and meta-analysis

Wenjiao Hu,
Hao Zhou,
Yue Zeng
et al.

Abstract: Introduction: This systematic review and meta-analysis aimed to assess the efficacy of acupuncture or moxibustion therapy in senile insomnia patients. Methods: A comprehensive literature search was conducted using 7 electronic databases to identify randomized controlled trials reported on the use of acupuncture or moxibustion therapy in insomnia. The time frame was set from database establishment to March 11, 2023. The RevMan (version 5.3) and STATA (ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…45 Finally, acupuncture may produce relaxation and calming effects that help reduce anxiety and improve sleep quality, providing support for the overall health and psychological well-being of patients. 46 Acupuncture has been widely used in the treatment of depression in recent years. Although its exact mechanism of action is not yet fully understood, a large number of studies have shown that acupuncture may exert antidepressant effects through several mechanisms.…”
Section: Acupuncturementioning
confidence: 99%
“…45 Finally, acupuncture may produce relaxation and calming effects that help reduce anxiety and improve sleep quality, providing support for the overall health and psychological well-being of patients. 46 Acupuncture has been widely used in the treatment of depression in recent years. Although its exact mechanism of action is not yet fully understood, a large number of studies have shown that acupuncture may exert antidepressant effects through several mechanisms.…”
Section: Acupuncturementioning
confidence: 99%